Managerial leadership in committees: a case study in a public rural combined school in the Ohangwena region, Namibia - Vaeta, Simon (Rhodes University, Faculty of Education, Department of Education, 2016)
The existing education legislations in Namibia call for school principals to put in place appropriate support mechanisms and create necessary internal conditions for leaders, including teachers who do not hold formal leadership positions, to exert their sphere of influence beyond the classroom and into school-wide leadership activities. The establishment of various committees in the school is to enhance and improve the performance of the school and to create a pleasant work environment and spirit of collaboration and teamwork (Namibia Ministry of Education, [MoE], 2005). Leadership in committees is one of the expectations of new education policy. The aim of this study was to explore the leadership practices within a range of committees in a public rural combined school in the Ohangwena region of Namibia. It further unpacked the purpose, roles and membership of each of the four committees; how these committees were established; what leadership functions the teachers as committee members exercised and what challenges inhibited their leadership practices within committees. The study provided recommendations for future research in the area of leadership practices in committees. This research is a case study. The study is designed within the qualitative interpretive paradigm. It is rooted in a social constructivist tradition and employs a range of data collection tools, namely document analysis, semi-structured interviews, observations and questionnaires to enhance the validity of findings. The study found that committees were established in line with the Namibian education legislation. However, the study found the principal lacked the experience and skills to use the committee system more effectively, and maintained the status quo. This resulted in the committees practising pure management responsibilities rather than leadership interest. The study also found that only the leadership tasks were distributed to the committees but the power was not distributed. It was revealed that committees were dormant; while they were named in school documents, they functioned variously, intermittently or not at all. The significance of the contradiction was there were no regulations to guide the conduct of committee members.
Keywords: Uncatalogued